Effect of beeswax content on hydroxypropyl methylcellulose-based edible film properties and postharvest quality of coated plums (Cv. Angeleno) - Navarro-Tarazaga, María L.; Massa, Alberto; Pérez-Gago, María B. (Elsevier, 2019)
The effect of beeswax (BW) content of hydroxypropyl methylcellulose (HPMC)eBW edible coatings on stand-alone film properties and on postharvest quality of coated ‘Angeleno’ plums was studied. The coatings contained BWat 4 lipid content levels (0, 20, 40 and 60 g/100 g, dry basis). Coated and uncoated plums were stored 4 weeks at 1 C and transferred to 20 C for 1e3 weeks. Addition of BW to the HPMC film matrix reduced film mechanical resistance and oxygen barrier, and improved film moisture barrier. Film mechanical properties showed a good fit with an exponential and/or linear model that could provide a useful tool to predict mechanical properties with others HPMCeBW composition mixtures. Coatings with BW reduced plum weight loss compared to HPMC-based coatings with no BW. Plum weight loss decreased as BW content increased from 20 to 40 g/100 g, but above 40 g/100 g BW content, weight loss was not further reduced. Whereas, water vapor permeability of stand-alone films decreased significantly as BW content increased to 60 g/100 g. Coatings reduced plum softening and bleeding, with those with lower BW content being more effective, which could be related to the ability of coatings to create a modified atmosphere in the fruit. Flavor was not affected by coating application. Results indicate that HPMCeBW coatings with 20 g/100 g BW would provide the best compromise to extend shelf life of ‘Angeleno’ plums.